The Impact of Preoperative Sarcopenia on Survival Prognosis in Patients Receiving Neoadjuvant Therapy for Esophageal Cancer: A Systematic Review and Meta-Analysis - Jin, Sheng-bo; Tian, Zi-bin; Ding, Xue-li; Guo, Ying-jie; Mao, Tao; Yu, Ya-nan; Wang, Kai-xuan; Jing, Xue (Frontiers in Oncology, 2021)
Sarcopenia is a demonstrated poor prognostic factor in patients with cancer. Neoadjuvant therapy (NACT) can improve the prognosis of patients with esophageal cancer (EC), but it also aggravated sarcopenia. Until now, the impact of preoperative sarcopenia on survival prognosis in patients receiving NACT for EC remains unclear. We systematically searched relevant studies in the PubMed, EMBASE, Web of Science, and The Cochrane Library databases up to March 8, 2020. Prevalence of sarcopenia before and after NACT, overall survival (OS) and disease-free survival (DFS) were collected for analysis. Finally, 11 cohort studies consisting of patients were included. Pooled analysis indicated that preoperative sarcopenia was associated with worse OS (HR = 1.290; 95% CI [1.078–1.543]; Z = 2.78; P = 0.005; I2 = 0.0%) and worse DFS (HR = 1.554; 95% CI [1.177–2.052]; Z = 3.11; P = 0.002; I2 = 0.0%) in the patients with EC received NACT. The prevalence of sarcopenia increased by 15.4% following NACT (ES=0.154; 95% CI [0.129–0.179]; Z = 12.05; P =0.047; I2 = 55.6%). Further subgroup analysis indicated that sarcopenia diagnosed following NACT (HR = 1.359; 95% CI [1.036–1.739]; Z = 2.44; P = 0.015; I2 = 6.9%) and age >65 years (HR = 1.381; 95% CI [1.090– 1.749]; Z = 2.68; P = 0.007; I2 = 0.0%) were independent risk factors for decreased OS. NACT can significantly improve the prognosis of patients with EC, however we should not ignore the impact of NACT on skeletal muscle mass, which leads to the deterioration of the prognosis of patients with EC. It is suggested that clinicians should pay attention to nutritional support, especially for EC patients during NACT.